Gambaran Jejaring Kerja Posyandu Lansia Dengan Rukun Warga di Wilayah Kerja Puskesmas Melur Pekanbaru Dalam Menunjang Pemberdayaan Masyarakat - T. Mohd Mirza; Tuti Restuastuti; Firdaus Firdaus (Fakultas Kedokteran Universitas Riau, 2018)
Community empowerment activities will be success if it is supported by the ability to build network. An ability to build a network is needed to get the support, that can be done during the interaction in work, such as building a good networking stage. This study aims to describe elderly community health care (ECHC) (posyandu lansia) networking with Rukun Warga (RW) in working area of Melur Pekanbaru Health Center. The study was qualitative descriptive, this study involving six main informants, three ECHC cadres and three RT heads and seven key informants, three heads of ECHC, three heads of RW and one head Puskesmas. Data were collected by in-depth interviews recorded with a voice recorder.The result showed the ECHC Network with RW can help to optimize the implementation of activities to support community empowerment as seen from elderly posyandu networking role with RW.